Characterization of photosynthetically synthesized poly(3-hydroxybutyrate) using a randomly mutated strain of Synechocystis sp. PCC 6714. Issue 1 (2nd January 2019) - Lackner, Maximilian; Kamravamanesh, Donya; Krampl, Margit; Itzinger, Regina; Paulik, Christian; Chodak, Ivan; Herwig, Christoph
ABSTRACT: Conventional polymers are made from fossil resources and consume fossil energy in their production, yielding CO2 emissions. Production of large-volume compounds from CO2, either from point sources or from the air, could reduce anthropogenic global warming. Poly(3-hydroxybutyrate) (PHB) is a biodegradable and biobased thermoplastic polymer which can be synthesized sustainably using CO2 . PHB exhibits a high crystallinity and shows properties similar to synthetic polyesters and also to polyolefins such as polypropylene. However, the low elongation at break and the brittleness of PHB are limitations, which, however, can be overcome by using other polyhydroxyalkanoates (PHA) as blends or copolymers. In this study, PHB produced by cyanobacteria from CO2 was extracted and characterized using various techniques. The Fourier Transform Infrared spectroscopy (FTIR) showed the characteristic signals expected for the phototrophic PHB. Differential Scanning Calorimetry (DSC) for thermal characterization of PHB showed a melting temperature of 151.42°C and 73.11°C for the crystallization process. From the Gel Permeation Chromatography (GPC) the molecular weight of cyanobacterial PHB was determined to be 1, 051, 900 g mol −1 . The analytics results show that the photosynthetically produced PHB ressembles conventional PHB from sugar fermentation, which is an established biopolymer today. It can be concluded that photosynthetically produced PHB has a strong market potential, backed by its sustainable production technology.